(untitled) (Journal of Informatics Education and Research, 2025)
It is difficult for many science and engineering undergraduate students to develop a visual image of the complicated, multi-stage process of 3D printing as an outcome of digital modeling to a piece of plastic. The old graphical models and discussions do not always tell the whole picture with regard to the dynamism in this technology. We have developed a new classroom experiment taking into consideration the "Gamixfication Reality" as a combination of both gamification challenges and immersive augmented reality (AR). The article provides a description of a new protocol of a practical activity in the classroom that enables students to work with smartphones or AR headsets and the Blippar application with a gamified module to have an opportunity to play with virtual 3D printer parts and processes. The experiment will aim at changing a challenging technical discussion into a fun, natural, and memorable learning process, enhancing understanding and an application.